Miniaturized Wideband Aperture Coupled Microstrip Patch Antenna by Using Inverted U-Slot - Amandeep Singh; Surinder Singh (International Journal of Antennas and Propagation)
This paper presents a linear polarized aperture coupled inverted U-slot patch antenna with small steps at the edges. The proposed design exhibits wideband behavior, acceptable return loss, VSWR, gain, small size, and less complexity. The theoretical analysis is based on the finite element method (FEM). This design has wide bandwidth, good return loss, VSWR, and radiation characteristics by implanting the inverted U-shaped stepped slots on a single aperture coupled patch. The proposed antenna design shows the measured return loss within acceptable range throughout the band (11.08 GHz–13.25 GHz) and maximum return loss is achieved with proper impedance matching. In this paper, the design considerations are presented and results are validated by the calculated and measured parameters.